2017
DOI: 10.1371/journal.pone.0168742
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis of Partial Retrograde Ejaculation in Non-Azoospermic Infertile Men with Low Semen Volume

Abstract: In non-azoospermic patients with low semen volume (LSV), looking for partial retrograde ejaculation (PRE) by searching sperm in the postejaculatory urine (PEU) is required. The use of a retro-ejaculatory index (R-ratio) was suggested to define PRE, but none of the studies indicated a specific threshold above which PRE must be considered. Our objective was to propose a threshold value for the R-ratio as indicative of PRE in patients with LSV selected to be devoid of any known causes or risk factors for retrogra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 35 publications
(54 reference statements)
0
8
0
Order By: Relevance
“…In a case-control study comparing 245 infertile men with a semen volume < 2 ml with 162 infertile men with a semen volume > 2 ml, 6% vs. 7% had sperm in the post-ejaculatory urine sample and was diagnosed with RE. 64 In a retrospective cohort study, involving 920 infertile men, RE was found in four (4%) out of 96 of azoospermic subjects. 65 …”
Section: Remarksmentioning
confidence: 99%
See 4 more Smart Citations
“…In a case-control study comparing 245 infertile men with a semen volume < 2 ml with 162 infertile men with a semen volume > 2 ml, 6% vs. 7% had sperm in the post-ejaculatory urine sample and was diagnosed with RE. 64 In a retrospective cohort study, involving 920 infertile men, RE was found in four (4%) out of 96 of azoospermic subjects. 65 …”
Section: Remarksmentioning
confidence: 99%
“…In a case-control study comparing 245 infertile men with a semen volume < 2 ml with 162 infertile men with a semen volume > 2 ml, 6% vs. 7% had sperm in the post-ejaculatory urine sample and was diagnosed with RE. 64 In a retrospective cohort study, involving 920 infertile men, RE was found in four (4%) out of 96 of azoospermic subjects. 65 Regarding anejaculation, Punab et al 10 showed that, in a large prospective clinical-epidemiological study investigating causes of male infertility, anejaculation accounted for 1.2% of all causes.…”
Section: Ejaculatory Dysfunctionsmentioning
confidence: 99%
See 3 more Smart Citations